1993
DOI: 10.1079/bjn19930045
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption and liver uptake of medium-chain fatty acids in non-anaesthetized pigs

Abstract: In order to study the rate of intestinal absorption and hepatic uptake of medium-chain fatty acids (MCFA), six growing pigs, mean body weight 65 kg, were fitted with a permanent fistula in the duodenum and with three catheters in the portal vein, carotid artery and hepatic vein respectively. Two electromagnetic flow probes were also set up, one around the portal vein and one around the hepatic artery. A mixture of octanoic and decanoic acids, esterified as medium-chain triacylglycerols, together with maltose d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
76
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 24 publications
7
76
0
Order By: Relevance
“…Several authors found relatively constant blood flow values after ingestion of the meal (Guillot et al, 1993;Guillot et al, 1994;Lang et al, 1999). One can easily assume that portal blood flow variations in the present work were similar for all the animals and that they consequently interfered in the same way for all the three diets.…”
Section: Portal Absorption Calculationssupporting
confidence: 63%
See 1 more Smart Citation
“…Several authors found relatively constant blood flow values after ingestion of the meal (Guillot et al, 1993;Guillot et al, 1994;Lang et al, 1999). One can easily assume that portal blood flow variations in the present work were similar for all the animals and that they consequently interfered in the same way for all the three diets.…”
Section: Portal Absorption Calculationssupporting
confidence: 63%
“…14 C meal absorption rate was calculated as: "portal absorption of 14 C / 14 C content in the meal". Blood flow per min and per kg body weight could be estimated thanks many references using growing pigs (Rérat et al, 1987;Simoes Nunes et al, 1989;Rérat et al, 1991;Rérat et al, 1992;Guillot et al, 1993;Guillot et al, 1994;Rérat et al, 1996;Santamaria et al, 1997;Lang et al, 1999;Le Floc'h et al, 1999;Vaugelade et al, 2000).…”
Section: Portal Absorption Calculationsmentioning
confidence: 99%
“…In fact, it is known that meal ingestion is followed by a small rise in portal blood flow during the first 1-2 postprandial hours and individual variations in pig portal blood flow have been established at between 2.8 and 5.7% [20]. Several authors found relatively constant blood flow values after ingestion of the meal [5,6]. One can easily assume that portal blood flow variations in the present work were similar for all the animals.…”
Section: Portal Absorption Calculationssupporting
confidence: 60%
“…A major proportion of the saturated fats of coconut oil are formed of medium chain fatty acids, which do not require a re-esterification process and are oxidized immediately for energy needs in the liver 1) . Due to this specific characteristic of medium chain fatty acids, it has also been reported that coconut oil cannot be ing oils on risk factors for coronary artery disease, such as oxidative stress and lipid peroxidation in rabbits.…”
Section: Introductionmentioning
confidence: 99%